Prinsip Pertumbuhan Gereja Mula-Mula Ditinjau Dari Kisah Para Rasul 2:1-47 Dan Aplikasinya Bagi Gereja Masa Kini - Ferderika Pertiwi Ndiy; S Susanto (Sekolah Tinggi Teologi Jaffray Jakarta, 2019)
Church growth is an important study in church history. The Bible has important principles in church growth, therefore these principles need to be analyzed so that they can contribute to the study of church growth. The Acts of the Apostles is a book that has a history and principles of church growth, therefore the author conducted research on church growth based on Acts 2: 1-47. The author uses a qualitative approach to literature study to find the principles of church growth based on Acts 2: 1-47. The results showed that there were three principles for the growth of the early church. The first principle based on the fourth verse is to depend on the Holy Spirit, the second principle based on verses 14-36, 42 is to preach the Word of God, the third principle based on verses 42-46 is to live in fellowship. For the growth of the church today the church must depend on the power of the Holy Spirit, teaching based on the word of God, and the church lives in fellowship.